Dysregulated expression of matrix metalloproteinases and their inhibitors may participate in the pathogenesis of pre-eclampsia and fetal growth restriction - Zhu, JiaYu; Zhong, Mei; Pang, ZhanJun; Yu, YanHong (Early human development, 2014)
Trophoblast invasion into the maternal endometrium serves an important function in human pregnancy. Dysregulation of the finely controlled process of trophoblast invasion can result in a wide spectrum of pregnancy abnormalities. We aimed to elucidate the relationship between the expression of matrix metalloproteinases and pregnancy complication. The study group consisted of placental bed biopsy tissues obtained from normal vaginal deliveries (N=15), normal cesarean deliveries (N=15), pre-eclampsia (N=24) and fetal growth restriction (FGR) (N=10). We evaluated the expressions of MMP-2, -8, -9, -11, -19, -15 (MT2-MMP), -16 (MT3-MMP), and -24 (MT5-MMP), as well as TIMP-1 and -3, by applying Western blot and immunohistochemistry methods. Human placental tissues were used for this study. The expressions of MMP-2, -8, -9, -11, -19, -15 (MT2-MMP), -16 (MT3-MMP), and -24 (MT5-MMP), as well as TIMP-1 and -3 in human placenta tissues. Compared with those in normal pregnancies, the expression of MMP-2, -8, -9 and -11 was downregulated in villous tissues of pre-eclampsia and FGR cases (p<0.05). TIMP-1 and -3 were increased in pre-eclampsia and FGR (p<0.05). No significant difference was found between normal vaginal deliveries and cesarean deliveries. We speculate that the change in invasion-associated proteinase expression will affect placental development and may thus contribute to the development of complicated pregnancies.